2021
DOI: 10.1007/s10549-021-06178-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival before and after the introduction of pertuzumab and T-DM1 in HER2-positive advanced breast cancer, a study of the SONABRE Registry

Abstract: Purpose Immediate and proper implementation of a new and more potent therapy is important to ensure that the patient achieves the best possible outcome. This study aimed to examine whether the real-world overall survival (OS) has improved in patients with human epidermal growth factor receptor 2-positive (HER2 +) advanced breast cancer (ABC) since the market release of pertuzumab and T-DM1. Furthermore, we aimed to assess the implementation and survival rates per hormone receptor (HR) subtype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Recently, a collaborative group from the Netherlands has examined whether the real-world OS improved in patients with HER2-positive advanced BC since the market release of pertuzumab and T-DM1. 25 The SOutheast Netherlands Advanced BREast cancer (SONABRE) registry included 493 systemically treated patients, who had been consecutively diagnosed with HER2-positive metastatic BC between 2008 and 2017. Outcome data confirmed that the survival of patients with HER2-positive advanced BC had significantly improved since the introduction of pertuzumab and T-DM1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a collaborative group from the Netherlands has examined whether the real-world OS improved in patients with HER2-positive advanced BC since the market release of pertuzumab and T-DM1. 25 The SOutheast Netherlands Advanced BREast cancer (SONABRE) registry included 493 systemically treated patients, who had been consecutively diagnosed with HER2-positive metastatic BC between 2008 and 2017. Outcome data confirmed that the survival of patients with HER2-positive advanced BC had significantly improved since the introduction of pertuzumab and T-DM1.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing OS calculated from second-line starting, independently on the type of first-line OS (months) treatment, patients treated with second-line T-DM1 (325 patients) had a 3-year OS of 40.8%, a 5-year OS of 26.9%, with a median OS of 29 months (95% CI, [23][24][25][26][27][28][29][30][31][32][33][34][35]. Patients treated with second-line lapatinib/capecitabine had a 3-year OS of 39.7% and a 5-year OS of 23.4%, with a median OS of 30 months (95% CI, 24.6-35.4).…”
Section: Characteristicsmentioning
confidence: 99%
“…Including different hospital types is considered a strength of this study. Nowadays, the PFS and OS are expected to be longer as reported in this study since an underuse of pertuzumab was observed in 2013 and 2014, whereas pertuzumab use was stable in 2015–2017 [ 8 ]. The OS is also expected to further increase due to new HER2-targeted treatment options [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…To present the use of systemic therapy, we reported first-given treatment regimens (HER2-targeted therapy, chemotherapy and/or endocrine therapy) and the use of systemic agents within the first five years from diagnosis (any HER2-targeted therapy, pertuzumab and T-DM1) per period using competing risk methodology [ 8 ]. Use of locoregional therapy (surgery of the primary tumour, and surgery and radiotherapy of a metastatic site) within the first year after diagnosis was determined per time period using competing risk methodology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation